PEMODELAN SISTEM USAHATANI TERINTEGRASI UNTUK MENDUKUNG PERTANIAN BERKELANJUTAN - I Wayan Budiasa (Bumi Lestari Journal of Environment, 2013)
AbstractThe objective of this study is to develop the optimal solution model for food productiontechnology of integrated farming system (SIMANTRI) to support sustainable agriculture inBali. Primary data under survey method towards 20 farmers of the SIMANTRI 068 in BulelengRegency and secondary data from appropriate sources were used to specify parameters ofthe model. Linear programming approach was used to analyze constrained optimizationproblem of the model by using BLPX88 package program. A small farming system with farmscale of 0.58 hectare, which integrates food and horticulture crops and bali cattle, wasoptimally operated by farmer. It is indicated by optimal solution of the model which conformsto observed behavior. The maximum farming system’ income that was generated from theoptimal model was Rp21,658,160 per annum. The integrated farming system (SIMANTRI068) is potentially sustainable since it can fulfil sustainability criteria: economically viable,environmentally sound, socially acceptable, technically and culturally appropriate.